Calcium phosphate cement for bone filler applications - Hablee, Sufiamie; Sopyan, Iis; Mel, Maizirwan; Mohd. Salleh, Hamzah; Rahman, Md Mujibur (Penerbit Akademia Baru, 2017)
Various formulations of calcium phosphate cement (CPC) have been developed to get cement paste with optimum setting times, injection capabilities, as well as mechanical and biological properties. This is important to ensure that CPC is applicable for clinical uses as bone filler materials. The existing studies on CPC have investigated factors affecting its properties which include liquid-to-powder ratio, types of solid and liquid phases used, concentration of liquid phase, and particle size of powder phase. One of the promising and interesting routes to improve properties of CPC is by incorporating polymeric additives as setting agents, such as gelatin, alginate, chitosan and hydroxypropyl methylcellulose. The aim of this paper is to review the recent developments of CPC for bone filler applications.